RECONCEPTUALIZING LEGAL PROTECTION FOR CUSTOMARY FORESTS: A MODEL FOR MITIGATING PALM OIL EXPANSION IN SOUTH KALIMANTAN - Muhammad Topan; Muhammad Akib; Boualaphiane Sisouk; Yulia Audina Sukmawan (Universitas Lampung, 2026)
This article reconceptualizes the legal protection of customary forests (customary forests) amid rapid palm oil expansion in South Kalimantan. The central issue is the legal vacuum and institutional fragmentation that hinder implementation of Constitutional Court Decision No. 35/PUU-X/2012, which redefined customary forests as non-state forests. The study examines the interaction between Law No. 41 of 1999 on Forestry and regulatory frameworks governing palm-oil-based energy projects that often overlook indigenous territorial rights. Using normative legal research with a socio-legal perspective, it analyzes national legislation, regional regulations, and cases involving tenure conflicts. The findings show that weak district-level recognition and the prioritization of biodiesel initiatives have pushed customary forests to a peripheral position in land governance. The article proposes an integrated protection model that treats customary forests as climate-critical commons and binding constraints in spatial planning and industrial licensing. The framework embeds co-governance and Free, Prior and Informed Consent to recognize indigenous communities as rights holders rather than victims of environmental harm, offering a subnational pathway for rights-based and environmentally just natural-resource governance.